Effectiveness of the Healthy Lifestyle Promotion Program for Yaquis with Obesity and Risk of Diabetes in the Short and Medium Term: A Translational Study - Castro-Juarez, Alejandro Arturo; Urquidez Romero, Rene; Serna-Gutiérrez, Araceli; Dórame-López, Norma Alicia; Solano-Morales, Mariela; Gallegos-Aguilar, Ana Cristina; Díaz-Zavala, Rolando Giovanni; Alemán-Mateo, Heliodoro; Campa-Quijada, Fernanda; Valenzuela-Guzmán, Diana Marcela; Esparza-Romero, Julián (2020)
Type 2 diabetes (T2D) is a public health problem worldwide, and the main risk factor for its development is obesity. The Yaqui ethnic group of Sonora has serious obesity problems, resulting in an increased risk of T2D in its inhabitants. The objective of this study was to evaluate the effectiveness of a health promotion program on obesity parameters and cardiovascular risk factors in short- (6 months) and medium-term periods (12 months) in indigenous Yaquis of Sonora. The design is a translational clinical study of a single cohort with prepost intervention measurements in a sample of 93 subjects. The effectiveness of the program was evaluated by comparing obesity parameters, metabolic markers, and physical activity 6 and 12 months with those measured under basal conditions using a paired t-test or Wilcoxon rank-sum test. The short-term retention percentage was 58.0%. There was a decrease in body weight (Δ = −3:9 kg, p ≤ 0:05) and other obesity parameters, and an increase in physical activity and improvements in metabolic markers (p ≤ 0:05) was observed. Similar findings were obtained for the medium-term period; body weight loss was also -3.9 kg (p ≤ 0:05). The short and medium-term results of the program showed improvements in the obesity parameters and other cardiovascular risk factors of the participants. These results support the effectiveness of the program and its translation in this ethnic group.